Momordica charantia L.—Diabetes-Related Bioactivities, Quality Control, and Safety Considerations - Çiçek, Serhat S. (Frontiers in Pharmacology, 2022)
Momordica charantia L. (Cucurbitaceae), commonly known as bitter gourd or bitter melon, is widely cultivated in many tropical and subtropical regions of the world, where its unripe fruits are eaten as a vegetable. Apart from its culinary use, M. charantia has a long history in traditional medicine, serving as stomachic, laxative or anthelmintic, and, most notably, for the treatment of diabetes and its complications. Its antidiabetic properties and its beneficial effects on blood glucose and lipid concentrations have been reported in numerous in vitro and in vivo studies, but the compounds responsible for the observed effects have not yet been adequately described. Early reports were made for charantin, a mixture of two sterol glucosides, and the polypeptide p-insulin, but their low concentrations in the fruits or their limited bioavailability cannot explain the observed therapeutic effects. Still, for many decades the search for more reasonable active principles was omitted. However, in the last years, research more and more focused on the particular cucurbitane-type triterpenoids abundant in the fruits and other parts of the plant. This mini review deals with compounds isolated from the bitter gourd and discusses their bioactivities in conjunction with eventual antidiabetic or adverse effects. Furthermore, methods for the quality control of bitter gourd fruits and preparations will be evaluated for their meaningfulness and their potential use in the standardization of commercial preparations.